Nutritional Interventions in Advanced Cancer: Scoping Review - Kenny, Ciaran; Eustace-Cook, Jessica (My University, 2026)
Background: It is unclear what evidence supports nutritional advice received by those with advanced cancer. In advanced cancer, the benefits of nutritional interventions are less clear, with no consensus about effectiveness. This uncertainty is compounded by the heterogeneity of nutritional interventions and absence of cohesive, evidence-based approaches. Intervention diversity highlights the need to summarize current dietary and nutritional approaches and their evidence base. Objective: To map and summarize the current evidence base for nutritional interventions in advanced cancer. Methods: A systematic search included studies on nutritional interventions in adults with advanced cancer, excluding enteral/parenteral nutrition. Five databases (CINAHL Ultimate, Embase, Medline, SCOPUS, Web of Science) were searched from inception until 10/20/2023. Four researchers undertook screening and data extraction. Due to the heterogeneous nature of the studies, data synthesis was narrative. Results: The databases search yielded 3290 records. Fifty additional publications were identified through manual searches. Title/abstract screening identified 253 articles for full-text screening, 35 of which met inclusion criteria. Of these, 25 (69%) were randomized controlled trials. The studies were separated into 5 themes: (1) nutraceutical and herbal interventions, (2) ketogenic diet, (3) nutrition advice/support, (4) oral nutrition supplements, (5) other nutritional interventions. Outcome measures reported included anthropometry, biological markers, feasibility, performance status, quality of life, survival, and treatment tolerability. Most provided information about weight and energy intake and a few reported lean body mass. Although some reported positive outcomes, evidence is insufficient for definitive recommendations for any of those interventions. Conclusions: Our scoping review provided limited evidence for various nutritional interventions and dietary approaches. Dietary advice and oral nutritional supplements sometimes appeared to enhance treatment tolerance and improve nutritional status; impact on overall survival was inconsistent. Nutraceutical and herbal interventions showed limited clinical benefits despite apparent biological activity. The variability in outcomes underscores the need for personalized nutritional strategies that consider individual patient factors.
PUBLISHED
Keywords: ketogenic diet, nutritional advice, supplements, neoplasms, nutraceutical and herbal interventions, nutrition support; Cancer; Swallowing Disorders